The Microbiome Tumor Axis: How the Microbiome Could Contribute to Clonal Heterogeneity and Disease Outcome in Pancreatic Cancer - Basu, Meghna; Philipp, Lisa-Marie; Baines, John F.; Sebens, Susanne (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant cancers. It is characterized by a poor prognosis with a 5-year survival rate of only around 10% and an ongoing increase in death rate. Due to the lack of early and specific symptoms, most patients are diagnosed at an advanced or even metastasized stage, essentially limiting curative treatment options. However, even curative resection of the primary tumor and adjuvant therapy often fails to provide a long-term survival benefit. One reason for this dismal situation can be seen in the evolution of therapy resistances. Furthermore, PDAC is characterized by high intratumor heterogeneity, pointing towards an abundance of cancer stem cells (CSCs), which are regarded as essential for tumor initiation and drug resistance. Additionally, it was shown that the gut microbiome is altered in PDAC patients, promotes Epithelial-Mesenchymal-Transition (EMT), determines responses towards chemotherapy, and affects survival in PDAC patients. Given the established links between CSCs and EMT as well as drug resistance, and the emerging role of the microbiome in PDAC, we postulate that the composition of the microbiome of PDAC patients is a critical determinant for the abundance and plasticity of CSC populations and thus tumor heterogeneity in PDAC. Unravelling this complex interplay might pave the way for novel treatment strategies.